Fostering Digital Entrepreneurship among Santri through Freelance Platform Workshops: A Community Service–Based Empowerment Program (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The rapid development of digital technology has opened new opportunities for online-based work, including freelance employment. However, many students in Islamic boarding schools (santri) still have limited awareness and skills to utilize these opportunities productively. This community service program aimed to foster digital entrepreneurial skills among santri through a workshop on the use of freelance platforms as a productive solution in the digital era. The program was implemented at an Islamic boarding school and involved a series of activities, including preparation, socialization, technical training, hands-on practice, simulation, mentoring, evaluation, and follow-up. The training focused on the use of freelance platforms such as Fiverr and Sribulancer, covering account creation, profile development, portfolio preparation, gig creation, and project bidding. Evaluation was conducted through direct observation, platform activity monitoring, and participant feedback. The results showed a significant improvement in participants’ digital literacy and readiness to engage in freelance activities. Most participants successfully created active freelance accounts, developed basic digital portfolios, and published service offerings on freelance platforms. Several participants also began to receive initial responses from potential clients, such as profile views, clicks, and service inquiries, indicating early engagement within the freelance ecosystem. Although not all participants secured projects, these interactions demonstrated meaningful progress for beginner freelancers. In conclusion, the program effectively enhanced santri’s digital skills and entrepreneurial awareness. The findings suggest that structured training combined with practical mentoring can empower santri to begin participating in the digital economy and support their long-term digital self-reliance. This program contributes to the limited literature on digital entrepreneurship empowerment in pesantren contexts by demonstrating the effectiveness of experiential freelance platform training based on observable engagement indicators such as account activity, portfolio development, and initial client interactions.